2013
DOI: 10.1163/15685411-00002684
|View full text |Cite
|
Sign up to set email alerts
|

Intraspecific variability and genetic structure in Meloidogyne chitwoodi from the USA

Abstract: Meloidogyne chitwoodi is a quarantine pathogen and a severe problem of potato. Intraspecific variation and genetic structure are not well characterised for M. chitwoodi, but are critical to avoid misidentification and to optimise management strategies. The objective of this study was to analyse the morphological and molecular variation of four M. chitwoodi isolates, representing all races and pathotypes currently known in the USA. Despite statistically significant morphological variation among adult females, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 29 publications
0
16
0
1
Order By: Relevance
“…[23,33]. However, the polymorphism of these markers is limited in comparison with mitochondrial DNA markers [4,48]. Recent studies suggest that nucleotide variations could be found in sequences from the M. graminicola mitochondrial amplification product ( [49]; Bellafiore et al, unpublished data).…”
Section: Diagnostic Molecular Markers To Identify M Graminicola and mentioning
confidence: 99%
See 1 more Smart Citation
“…[23,33]. However, the polymorphism of these markers is limited in comparison with mitochondrial DNA markers [4,48]. Recent studies suggest that nucleotide variations could be found in sequences from the M. graminicola mitochondrial amplification product ( [49]; Bellafiore et al, unpublished data).…”
Section: Diagnostic Molecular Markers To Identify M Graminicola and mentioning
confidence: 99%
“…The Meloidogyne genus therefore appears as a model system to investigate the impact of each reproduction system on the maintenance of genetic diversity and intraspecific variability in correlation to the pathogenicity [3]. For instance, M. chitwoodi, a meiotic parthenogenetic nematode, has a wide host range and has shown to have significant intraspecific variability and genetic structure between four populations from the USA [4]. In addition, several obligatory mitotic parthenogenetic nematodes having a larger host range were studied (e.g., M. enterolobii), and were characterized by a genetically homogeneous organization [5].…”
Section: Introductionmentioning
confidence: 99%
“…Meloidogyne chitwoodi isolates studied include WAMCl (race 1), WAMCRoza (race 1, pathotype Roza), WAMC27 (race 2), and CAMC2 (race 2, pathotype California) (Brown et al, 2009;Humphreys-Pereira & Elling, 2013). Nematodes were propagated on tomato cv.…”
Section: Nematode Culturesmentioning
confidence: 99%
“…As part of the same study, we analysed the genetic diversity of M. chitwoodi based on mitochondrial DNA and found that this nematode is very heteroplasmic. Distinct isolates showed a weak genetic structure, indicative of gene flow and sexual reproduction between populations under field conditions or a common founder population (Humphreys-Pereira & Elling, 2013). This is an important finding because exchange of genetic material between M. chitwoodi populations in the field could explain isolate-specific variability in virulence.…”
mentioning
confidence: 94%
See 1 more Smart Citation